Revealing the rhetorical moves and linguistic patterns in discipline-related undergraduate thesis - Risa Rumentha Simanjuntak (UNIB Press, 2022)
Previous studies have provided exciting findings for language variations in theses and dissertations. However, not many studies have revealed the rhetorical analysis of the undergraduate abstracts. This study investigated the rhetorical structure of undergraduate thesis abstracts to reveal the constructions of the genre by novice writers. It further explored the variations between two groups of writers, students with the native language of English and Indonesian students writing in English. The aim was to present the commonalities and differences within the genre and finally conclude the genre’s conventions. The corpus for this study consisted of 180 undergraduate thesis abstracts from 12 universities in the United States, New Zealand, and Indonesia from Computer Science. The findings of this study revealed certain conventions consisting of rhetorical moves and rhetorical strategies used to perform the rhetorical moves. Differences between native writers of English and non-native writers of English included the use of lexical items and lexico-grammatical constructions in presenting arguments and evidence. The study concluded that socio-cultural factors, such as institutional guidelines for thesis writing and students’ first language, may contribute to the genre's variations.